2023
DOI: 10.1111/plb.13499
|View full text |Cite
|
Sign up to set email alerts
|

Do photosynthetic metabolism and habitat influence foliar water uptake in orchids?

Abstract: Epiphytic and rupicolous plants inhabit environments with limited water resources.Such plants commonly use Crassulacean Acid Metabolism (CAM), a photosynthetic pathway that accumulates organic acids in cell vacuoles at night, so reducing their leaf water potential and favouring water absorption. Foliar water uptake (FWU) aids plant survival during drought events in environments with high water deficits. We hypothesized that FWU represents a strategy employed by epiphytic and rupicolous orchids for water acquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…During the whole growth period, the response of the leaf structure and physiology of male and female P. euphratica to humidification exhibited both similarities and differences. In addition to WUE, there was a positive correlation between predawn water potential and photosynthetic capacity in male and female P. euphratica, indicating that an improvement in leaf water status due to humidification was beneficial to the process of carbon assimilation [59]. After comparing the fluorescence parameters, we found that qP and ETR were negatively correlated with the leaf predawn water potential.…”
Section: Response Of Leaf Ecophysiology To Wettingmentioning
confidence: 81%
“…During the whole growth period, the response of the leaf structure and physiology of male and female P. euphratica to humidification exhibited both similarities and differences. In addition to WUE, there was a positive correlation between predawn water potential and photosynthetic capacity in male and female P. euphratica, indicating that an improvement in leaf water status due to humidification was beneficial to the process of carbon assimilation [59]. After comparing the fluorescence parameters, we found that qP and ETR were negatively correlated with the leaf predawn water potential.…”
Section: Response Of Leaf Ecophysiology To Wettingmentioning
confidence: 81%
“…As hypothesised by Berry et al (2019), differences in C should influence FWU, with high values of C resulting in relatively constant FWU rates that can be sustained for longer. In fact, a trade‐off between C and FWU has been suggested, whereby species with high C usually exhibit lower FWU capacities and/or rates (Gotsch et al, 2015; Lima et al, 2023). However, under drought conditions and declining leaf Ψ, a higher C implies that succulents capable of FWU such as Crassula will be able to absorb greater amounts of atmospheric water to buffer Ψ.…”
Section: Discussionmentioning
confidence: 99%
“…and Sedum, have only marginal hydathodes or a single (sub)apical one (Caballero & Jiménez, 1977;'t Hart & Bleij, 2003;Moreira et al, 2012;Thiede & Eggli, 2007), and even though there are reports of laminar hydathodes in some Cotyledon species (Weingart, 1935) constant FWU rates that can be sustained for longer. In fact, a tradeoff between C and FWU has been suggested, whereby species with high C usually exhibit lower FWU capacities and/or rates (Gotsch et al, 2015;Lima et al, 2023). However, under drought conditions and declining leaf Ψ, a higher C implies that succulents capable of FWU such as Crassula will be able to absorb greater amounts of atmospheric water to buffer Ψ.…”
Section: Hydathode-mediated Foliar Water Uptakementioning
confidence: 99%
See 1 more Smart Citation